Memahami kehendak pelanggan perkhidmatan bas awam menggunakan SERVQUAL dan model Kano - Liong, Choong Yeun; Zainol Mustafa,; Wan Norsiah Mohamed,; Lee , Poi Woon (Penerbit ukm, 2007)

(untitled)
In Malaysia, bus is one of the most important public transport especially in linking housing areas to cities. Customer satisfaction and important attributes of public bus service have to be identified in order to encourage its usage. This paper reports on the integrated approach of SERVQUAL and Kano model to categorise a major public bus service attributes and their customer satisfaction in order to maintain the strong attributes and to improve on the weak ones based on the resulted Kano categories. This paper also discusses the steps towards decision making based on the integration of SERVQUAL and the Kano’s model so that they complement each other. Such approach aims to help the service provider to not only be able to measure their customer satisfaction, but also to prioritise improvement efforts in order to strengthen the weak attributes, and to expedite the development of innovative services through the identification of attractive attributes and to improve on them in the future. A total of 150 sets of questionnaire, which consist of demography, SERVQUAL and Kano’s parts, have been administered in the Klang Valley, and a total of 133 sets of that have been filled up completely and were analysed using SPSS and Kano’s classification. Analyses by gender and ethnic have also been done. Finally results of the analyses and a number of suggestions for improvement based on the findings are given